Distribution of metals and radionuclides in the lichens Cladonia rangiferina and C. mitis from the past uranium mining region of Elliot Lake, Ontario, Canada. Issue 12 (December 2022) - Anderson, J.; Caron, F.; Beckett, P.; Spiers, G.A.; Lévesque, N.; Charbonneau, G.M.; Halvorson, B.; Dufour, H.; Lock, A.
Abstract: The present study was performed in the Elliot Lake area (Ontario, Canada), a site of uranium mining and milling for nearly 40 years between 1950's and 1990's. Although mining activities ceased in the mid-1990's, the site hosts several tailings management areas (TMAs) which are under ongoing rehabilitation and monitoring. Several surveys using lichens as a biomonitoring tool were completed in the 1980s and the 1990s to assess the levels of contaminants. The present survey aimed to re-visit the historical surveys, and to determine the current status of environmental recovery of the area. Our survey consisted of sampling two lichen species, Cladonia rangiferina and C. mitis, in an area covering up to 50 km from the former mining operation and the TMAs. The results reported in this work indicated that the levels of metals and radionuclides, diagnostic of mining operations, have decreased over time: particularly, the U, Th and Pb levels in both lichen species dropped by about two orders of magnitude by the 2020's compared to the 1980's. Likewise, the Cs-137 levels in both lichen species reflect present day global background. The study provides a new set of present-day regional baseline elemental concentrations for other metals that are associated with mining (Cd, As, Ti, Cs). Finally, there were weak but statistically significant differences in the levels of some elements (U, Th, Cd) between the two lichens, suggesting these two species might have different capture mechanisms or retention abilities. Highlights: Metals levels in lichens have decreased in a survey 40 years after mine closure. A new baseline was obtained for U, Th, Pb, As, Cd, Ti and Cs for lichens in the area. Cs-137 levels in the lichens reflect worldwide present-day background values. The capture rate of elements is slightly different in C. rangiferina vs C. mitis . Abstract : Natural radionuclides; Artificial radionuclides; Terricolous lichens; Environmental recovery; Historical mining; Metal contamination.